Postoperative pain and respiratory function in patients treated with electroacupuncture following coronary surgery - Colak, Mehmet C.; Kavakli, Ahmet; Kilinc, Abdulgani; Rahman, Ali (Riyadh Armed Forces Hospital, 2010)
Objectives: To evaluate respiratory function and pain score in patients undergoing coronary bypass procedures during the first 7 postoperative days. Methods: The study was carried out as a case-control study between April 2008 and April 2009 in the Department of Cardiovascular Surgery, Firat University Faculty of Medicine, Elazig, Turkey. Thirty patients, who had undergone a median sternotomy (MS) for coronary artery bypass graft, were randomized to either the electroacupuncture and pharmacologic analgesia (acupuncture) group, or the pharmacologic analgesia alone (control) group. In each group, severity of pain, analgesic intake, respiratory function, and pulmonary complications were recorded. Pethidine hydrochloride and metamizole sodium were administered. Results: Of the 30 subjects, 15 were in the control group and 15 in the acupuncture group. there were no statistically significant differences between the 2 groups in terms of age and gender. Statistically significant differences in metamizole, pethidine, days 3, 5, 6, and 7 visual analogue scale scores were observed between the acupuncture and control groups. Postoperative complications (atelectasia) were observed in 2 (13.3%) patients, one (6.6%) in each group. The postoperative forced expiratory volume in one second /forced vital capacity value was higher than the preoperative value in the acupuncture group. Conclusions: Electroacupuncture was more effective than control treatments in decreasing pain and limiting opioid and non-opioid medication intake during the first 7 postoperative days following MS.
Keywords: Cardiac-Surgery; Acupuncture; Dysfunction; Management; Infusion; Bypass